Analysis Of The Influence Of Perceived Risk And Trust On Customers' Purchase Intention At Tokopedia.Com - Silvia Ekasari; Arifin Djakasaputra; Luh Komang Candra Dewi; Tanti Widia Nurdiani; Erina Alimin (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
E-retailing, sometimes known as online shopping, is the practice of purchasing or selling things using the internet. People's preferences for making purchases or shopping online can be influenced by a variety of factors, including psychological, social, emotional, and privacy-related ones. Determining the impact of perceived risk and trust on intentions to shop online is the goal of the study. Multiple regression analysis is a quantitative method used in this study. The study's target population consists of online shoppers who have completed at least one online purchase within the past year. One hundred persons made up the study's sample. This study employed non-probability sampling as its method of sampling. A scale specifically designed to gauge intentions for online buying was created independently and modified according to behavior, goals, situations, and time. In the meanwhile, a scale with three dimensions ability, benevolence, and integrity is used to assess trust, and a scale with five dimensions financial, product, time, delivery, social, and information security risks is used to measure perceived risk. The study's findings indicate that intentions to shop online are significantly influenced by perceived risk and trust. The benevolence dimension of trust and the product risk dimension of perceived risk were the two variables whose regression coefficient values were significant, as determined by the results of the minor hypothesis test of the significance of each regression coefficient on the dependent variable.